Daily activity pattern in spring of Liolaemus nigroviridis (Squamata: Liolaemidae), a sky island lizard of the Andes mountains - Jorge Mella; Jorge Mella-Romero; Juan Luis Allendes (Gayana)
This work presents the daily activity pattern in spring of Liolaemus nigroviridis Müller & Hellmich, 1932, a sky island lizard of the Andes. Behavioral data were recorded and analyzed for L. nigroviridis in Farellones (central Chile) during the spring season. The pattern for adult lizards was unimodal, with a higher concentration of specimens observed between 13:00 and 14:00 pm. Juveniles presented a relatively constant activity during the day. The results may be explained by seasonality and the thermoregulatory behavior of the species.